Development of a Two-Stage Pyrolysis Process for the End-Of-Life Nickel Cobalt Manganese Lithium Battery Recycling from Electric Vehicles - Lingyun Zhu (Sustainability, 2020)
With the continuous promotion of electric vehicles, the pressure to scrap vehicle batteries is increasing, especially in China, where nickel cobalt manganese lithium (NCM) batteries have gradually come to occupy a dominant position in the battery market. In this study, we propose a two-stage pyrolysis process for vehicle batteries, which aims to effectively deal with the volatilization of organic solvents, the decomposition of lithium salts in the electrolyte and the removal of the separator material and polyvinylidene fluoride (PVDF) during battery recycling. By solving these issues, recycling is more effective, safe. Through thermogravimetric analysis (TGA), the pyrolysis characteristics of the battery’s internal materials are discussed, and 150 °C and 450 °C were determined as the pyrolysis temperatures of the two-stage pyrolysis process. The results show that in the first stage of pyrolysis, organic solvents EC (C4H3O3), DEC (C5H10O3) and EMC (C4H8O3) can be separated from the electrolyte. In the second stage, the pyrolysis can lead to the separator’s thermal decomposition. The gas products are alkane C2-C6, and the tar products are organic hydrocarbons C15-C36. Meanwhile, the solid residue of the battery’s internal material seems to be very homogeneous. Finally, the potential recovery value and pollution control countermeasures of the products and residues from the pyrolysis process are analyzed. Consequently, this method can effectively handle NCM vehicle battery recycling, which provides the basis for the subsequent hydrometallurgical or pyrometallurgical process for element recovery of the battery material.